Faktor Yang Mempengaruhi Permasalahan Desa Taba Terunjam Terhadap Perkembangan Dengan Menggunakan Video Profil - Fadilah, Fadilah; Ibrahim, Agung Biladin; Anugrah, Bintang Melgian; Kulsum, Umi; Azizah, Wafiq; Astari, Syirli; Saputra, Yogy Ardian; Virizky, Fayzha; Syaufuri, Intan Lhotifah; DK, Sonia; Lestari, Andes (Pakis Journal Institute, 2024)
This article describes the use of documentary videos as an effective tool for the introduction of Taba Terunjam Village, Karang Tinggi District, Central Bengkulu Regency. This article discusses how documentary videos can be used to introduce the potential and unique characteristics of a village to a wider audience, including tourists and potential investors. With a visual approach that is interesting to look at, documentary videos can highlight aspects of the culture, history and natural riches of the village. In addition, this article explores documentary video making techniques, the challenges faced, and the benefits that villages can gain from video-based promotion. In conclusion, documentary video is a method that has great potential in promoting and raising the profile of villages in the context of globalization and digitalization.